Programming 8-bit PIC microcontrollers in C : with interactive hardware simulation - Bates, Martin, 1952- (Elsevier/Newnes, 2008)
"PIC microcontrollers are present in almost every new electronic application that is released to market. With the proliferation of the PIC, more engineers and engineering students need to understand how to design, develop, and build with them. Martin Bates, best-selling author, has provided a step-by-step guide to programming these microcontrollers (MCUs) with the C programming language. This book is perfect for new professionals, students, and hobbyists who have not previously worked with PICs, since no prior knowledge of C is necessary to understand the book. Included within the text are lots of source code, circuit schematics, and hardware block diagrams."--Jacket.